Underreliance on Mechanistic Models: Comment on Ferguson (2015). - Tryon, Warren W. (American Psychologist, 2016)
Ferguson (2015) proposed that our overreliance on mechanistic models is responsible for the public's negative view of psychology. On the contrary, I claim that our explanations do not actually explain because they lack mechanism information and that is why the public has a negative view of psychology. Some of the mechanism information required to move from interpretations to explanations can be found in parallel distributed processing connectionist neural network models of psychology and behavior.